Phase transformations at reduction of corundum - Dan`ko, A.Ya.; Rom, M.A.; Sidelnikova, N.S.; Kaltaev, Kh.Sh.; Nizhankovsky, S.V.; Fedorov, A.I. (Functional Materials, 2007)
Research results are presented on the corundum structure transformation caused by reducing annealing. The annealing at 1500-2000°C in Ar atmosphere at CO + H₂ concentration 0.1-10 vol.% and N₂ 0.1-0.4 vol.% has been found to result in the corundum transformation into aluminum oxynitride compounds with the spinel structure (γ-A1ON) with the unit cell period of about 7.932 to 7.948 A and wurtzite (AIN) with a≈3,107- 3,115 and c≈4,979-4,988 A. Possible mechanisms of the transformations are discussed.